Effect of emergency department fast track on emergency department length of stay: a case–control study. Issue 12 (25th November 2008) - Considine, J; Kropman, M; Kelly, E; Winter, C
Abstract : Objective: To examine the effect of fast track on emergency department (ED) length of stay (LOS). Design and setting: Pair-matched case–control design in a public teaching hospital in metropolitan Melbourne, Australia. Participants: Patients treated by the ED fast track (cases) between 1 January and 31 March 2007 were compared with patients treated by the usual ED processes (controls) from 1 July to 15 November 2006 (n  =  822 matched pairs). Intervention: ED fast track was established in November 2006 and focused on the management of patients with non-urgent complaints. Main outcome measures: The primary outcome measure was ED LOS for fast-track patients. Secondary outcomes were waiting times and ED LOS for other ED patients. Results: Median ED LOS for non-admitted patients was 132 minutes (interquartile range (IQR) 83–205.25) for controls and 116 minutes (IQR 75.5–159.0) for cases (p<0.01). Fast-track patients had a significantly higher incidence of discharge within 2 h (53% vs 44%, p<0.01) and 4 h (92% vs 84%, p<0.01). Conclusions: ED fast track decreased ED LOS for non-admitted patients without compromising waiting times and ED LOS for other ED patients.